The Significance for Indonesian Democratic Value Integrated to Learning English Correspondence of International Private Law Course Subject at University - Pamuji, Wirawan; Hidayat, Ahmad (Indonesian Journal of Contemporary Multidisciplinary Research, 2023)
International Private Law Course Subject contains about how students of Law understand and comprehend the application for realizing International Law Standards about preceding demanding and arguing Law Argumentation in written context. The English materials for private law needs an urgency to read a case text for court English Letter as an International Correspondent to Explain the meaning By collecting steps of Teaching with Literal Data, Researcher develops arguments with Descriptive Qualitative Research.  The Subject can infer Contextual Application as International Private Law Material Instead of Correspondence Application with Inquiry Strategy